Crossing the Topographies of Modernity in the U.S.-Mexico Borderlands: Towards an Ethnography of “Out of Place” Ideas - Thomas Kramsch, Olivier (Frontera Norte, 2017)
As the national economies of Mexico and the United States intertwine more tightly under NAFTA, the role of the U.S.-Mexico border as a catalyst for wider economic development has emerged as a central preoccupation of the administrations of Vicente Fox and George W. Bush. Yet, the sociocultural and intellectual contexts for successful cross-border development are riven by discrepant visions of the political possibilities inherent in achieving authentic transboundary integration. Drawing on recent key English- and Spanish-language works, the author attempts to account for this discrepancy in the transboundary spatial imagination by rooting observed discourses in diverging traditions of modernity, modernism, and modernization, focusing on the Latin American intellectual negotiation of the postmodern condition. Rather than celebrate the U.S. Mexico border as a postmodern space of radical openness or defend its position as a vital bulwark against the dissolution of “heroic” nation-state building projects, the article attempts to view both sets of discourses from a fragile middle-ground, hinting at possible linkages (and solidarities) with other, non-Western, “peripheral” modernities. RESUMEN En el ámbito de una cada vez más acelerada integración entre México y los Estados Unidos propiciada por el Tratado de Libre Comercio, el papel de la frontera entre ambos países como catalizador de un desarrollo económico más amplio ha emergido como una preocupación central para ambos gobiernos. Sin embargo, como sugiere este ensayo, los contextos socioculturales e intelectuales para el desarrollo transfronterizo se caracterizan por enfoques distintos de las posibilidades políticas inherentes a una auténtica integración transfronteriza. El autor intenta explicar las razones de esta discrepancia, buscando en discursos que encuentran sus raíces en tradiciones divergentes de modernidad, modernismo y modernización, haciendo hincapié en la negociación intelectual latinoamericana de la condición posmoderna. En lugar de concebir la frontera entre Estados Unidos y México como espacio posmoderno de apertura radical o defender su rol como baluarte inviolable contra la disolución de proyectos “heroicos” dirigidos hacia la construcción del Estado-nación, el ensayo abarca ambos discursos desde el punto de vista de un espacio intermedio y todavía frágil, además de indicar posibles vínculos (y solidaridades) con otras modernidades “incompletas” que perviven de manera marginal en Occidente.